2020
DOI: 10.3389/fmicb.2020.614194
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Traits Correlate With Resistance to Predation by Protists in Soil Pseudomonads

Abstract: Root-colonizing bacteria can support plant growth and help fend off pathogens. It is clear that such bacteria benefit from plant-derived carbon, but it remains ambiguous why they invest in plant-beneficial traits. We suggest that selection via protist predation contributes to recruitment of plant-beneficial traits in rhizosphere bacteria. To this end, we examined the extent to which bacterial traits associated with pathogen inhibition coincide with resistance to protist predation. We investigated the resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 82 publications
(117 reference statements)
2
18
0
Order By: Relevance
“…There is increasing evidence that predator-prey dynamics of bacterivores contribute significantly to the deterministic processes that eventually determine microbiome composition and function (Rosenberg et al, 2009;Amacker et al, 2020;Rüger et al, 2021). Numbers of bacterivore protists show a steep increase toward the plant rhizosphere, where protist predation regulates bacterial turnover (Zwart et al, 1994;Alphei et al, 1996).…”
Section: Predator-prey Dynamics and Microbiome Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence that predator-prey dynamics of bacterivores contribute significantly to the deterministic processes that eventually determine microbiome composition and function (Rosenberg et al, 2009;Amacker et al, 2020;Rüger et al, 2021). Numbers of bacterivore protists show a steep increase toward the plant rhizosphere, where protist predation regulates bacterial turnover (Zwart et al, 1994;Alphei et al, 1996).…”
Section: Predator-prey Dynamics and Microbiome Assemblymentioning
confidence: 99%
“…Few experiments to date studied how increased species richness of protistan predators feeds back on bacterial diversity and function. Single protist taxa differ in their feeding modes ( Glücksman et al, 2010 ; Flues et al, 2017 ; Amacker et al, 2020 ), and higher species richness was shown to strongly increase the exploitation of bacterial prey species ( Saleem et al, 2012 , 2013 ; Hünninghaus et al, 2017 ). It appears that protistan predation is enhancing bacterial biocontrol activity on roots ( Weidner et al, 2016 ; Xiong et al, 2018 ; Gao et al, 2019 ; Amacker et al, 2020 ).…”
Section: Predator-prey Dynamics and Microbiome Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…bacterivorous protists (Mueller and Mueller 1970;Bamforth 1973Bamforth , 2007Bamforth , 2010Flues, Bass and Bonkowski 2017). Protistan predation has a profound influence on the structure and function of bacterial communities (Matz and Kjelleberg 2005;Krome et al 2010;Jousset 2012;Amacker et al 2020). Since these microbial eukaryotes comprise a vast array of functional traits in morphologies, locomotion and feeding modes (Fiore-Donno et al 2019;Dumack et al 2020), we presume that different protistan taxa play contrasting or complementary ecological roles within the heterogeneous habitat of forest canopy.…”
Section: Introductionmentioning
confidence: 99%
“…Protistan predation has a profound influence on the structure and function of bacterial communities (Matz and Kjelleberg 2005; Krome et al . 2010; Jousset 2012; Amacker et al . 2020).…”
Section: Introductionmentioning
confidence: 99%